Stone blind : a novel - Haynes, Natalie (Harper, an imprint of HarperCollinsPublishers, 2023)
"The only mortal in a family of gods, Medusa is the youngest of the Gorgon sisters. Unlike her siblings, Medusa grows older, experiences change, feels weakness. Her mortal lifespan gives her an urgency that her family will never know. When the sea god Poseidon assaults Medusa in Athene's temple, the goddess is enraged. Furious by the violation of her sacred space, Athene takes revenge--on the young woman. Punished for Poseidon's actions, Medusa is forever transformed. Writhing snakes replace her hair and her gaze will turn any living creature to stone. Cursed with the power to destroy all she loves with one look, Medusa condemns herself to a life of solitude. Until Perseus embarks upon a fateful quest to fetch the head of a Gorgon"--